Emerging Strategies of Nanomaterial‐Mediated Tumor Radiosensitization. Issue 3 (29th August 2018) - Xie, Jiani; Gong, Linji; Zhu, Shuang; Yong, Yuan; Gu, Zhanjun; Zhao, Yuliang
Abstract: Nano‐radiosensitization has been a hot concept for the past ten years, and the nanomaterial‐mediated tumor radiosensitization method is mainly focused on increasing intracellular radiation deposition by high atomic number (high Z) nanomaterials, particularly gold (Au)‐mediated radiation enhancement. Recently, various new nanomaterial‐mediated radiosensitive approaches have been successively reported, such as catalyzing reactive oxygen species (ROS) generation, consuming intracellular reduced glutathione (GSH), overcoming tumor hypoxia, and various synergistic radiotherapy ways. These strategies may open a new avenue for enhancing the radiotherapeutic effect and avoiding its side effects. Nevertheless, reviews systematically summarizing these newly emerging methods and their radiosensitive mechanisms are still rare. Therefore, the general strategies of nanomaterial‐mediated tumor radiosensitization are comprehensively summarized, particularly aiming at introducing the emerging radiosensitive methods. The strategies are divided into three general parts. First, methods on account of the intrinsic radiosensitive properties of nanoradiosensitizers for radiosensitization are highlighted. Then, newly developed synergistic strategies based on multifunctional nanomaterials for enhancing radiotherapy efficacy are emphasized. Third, nanomaterial‐mediated radioprotection approaches for increasing the radiotherapeutic ratio are discussed. Importantly, the clinical translation of nanomaterial‐mediated tumor radiosensitization is also covered. Finally, further challenges and outlooks in this field are discussed. Abstract : The general strategies for nanomaterial‐mediated tumor radiosensitization reported to date are comprehensively summarized, covering three aspects: 1) enhancing the radiosensitivity of tumors by nanoradiosensitizers with intrinsic radiosensitive properties, 2) nanomaterial‐mediated synergistic radiotherapy, and 3) protecting healthy tissues from radiation‐caused injury by nanoradioprotectors.